Writing as a means of exploration in students’ conceptual understanding: From scribbles to understanding - Wardiah, Dessy; Kristiawan, Muhammad (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the role of writing as a tool for enhancing students’ conceptual understanding and critical thinking across various academic disciplines. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to identify and analyze relevant studies. Six primary research articles were selected based on rigorous inclusion criteria to explore the effectiveness of writing-based learning strategies. The review reveals that writing strategies such as exploratory writing, reflective journaling, and writing-based discussions promote higher-order thinking skills by enabling students to organize information, reflect critically, and connect new concepts with prior knowledge. In literacy and language, writing fosters cultural and social awareness, while in mathematics and science, it facilitates the articulation of abstract concepts. Writing is not only a communication tool but also a powerful medium for cognitive development and conceptual understanding in education. These findings suggest that educators should integrate writing into instructional strategies across disciplines to enhance student engagement and learning outcomes. However, the review highlights the need for further empirical research with larger samples and robust methodologies to validate these conclusions.